The relationship between human resource practices and employee retention in manufacturing industry - Parameswary, Kerisnasamy (2024)
Retention of talents is crucial for organizations to remain competitive in the business. Hence, employee retention has received considerable research attention including the various long-term strategies and efforts performed by the organization to ensure that employees remain in the business. The study aims to examine the relationship between four human resource practices (training and development, career development, rewards and compensation, performance appraisal) and employee retention. The study was conducted among 170 employees selected from five manufacturing companies located in Penang, Malaysia. The respondents for this study were selected using a convenient sampling technique. This study employed a quantitative research approach, based on cross-sectional study research design. The data for this study were collected using the online survey via Google forms. The data was analyzed using Statistical Package for Social Science (SPSS) version 27. Both the descriptive and inferential analysis was performed to fulfil the objective of the study. The multiple regression analysis indicates that rewards and compensation and performance appraisal are strongly correlated with employee retention. However, training and development and career development do not have a statistically significant relationship with employee retention in the manufacturing companies. This study has also identified practical implications, theoretical implications, and limitations encountered during its execution. This study also proposed recommendations for future researchers interested in investigating the correlation between HR practices and employee retention.